Experimental Study on the Use of Thermoelectric Generators in Harvesting Human Body Heat - Rosli, N.; Mohamed, H. (International Journal of Engineering and Technology, 2018)
The objective of this work is to investigate the potential use of a thermoelectric generator (TEG) in harvesting human body heat at four body locations namely forehead, wrist, palm and calf for different human activities in Malaysia. Important parameters for this experiment are human body temperature, room temperature, output voltage, output resistance and output power. A healthy male and female perform a series of activities including resting, walking and running for 10 minutes in an indoor setting. Results indicate the relevant effects of temperature and movement on producing power from human body heat. Different parts of the body have different temperatures, thus creating different output powers. Results show that as the movement increases, the human body temperature and the amount of energy harvested also increase. It is also observed that forehead provides the highest amount of power generated during running activity. When the body temperature is above 35 Â°C, the TEG can generate power more than 5.0 mW. The highest power generated during the experiment is 9.5 mW. Even though Malaysia is known as a hot and humid region, TEGs can be feasibly utilized as a wearable device that converts human heat energy into electrical energy.
Keywords: heat; renewable energy; skin temperature; thermoelectric generators; wearable device